Morphogenetic Properties Of Grass-Gray Soils (Texas Journal of Agriculture and Biological Sciences, 2022)
Origin, distribution, relief of gray oasis soils in the territory of Surkhandarya region, lithologicalgeomorphological, hydrogeological conditions of the studied area and soil-forming factors and morphological features of soils, mechanical composition, nutrient supply.